2017
DOI: 10.1007/s11060-017-2577-7
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of chemoradiation following index craniotomy is associated with decreased survival in high-grade glioma

Abstract: The Stupp protocol of post-resection external beam radiation therapy and concomitant temozolomide is the standard of care for patients with newly-diagnosed glioblastoma, with expanded use in anaplastic astrocytoma. However, the optimal interval between surgery and these adjuvant therapies, and its impact on survival, is unknown. To investigate this, de-identified claims from a large, private health insurance database were queried to identify adult patients who underwent index craniotomy for resection of a supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
0
21
2
2
Order By: Relevance
“…The most representative article published by Nathan [27] ,which included 2,535 patients with high-grade glioma and was divided into three groups according to different time intervals (0-28d, 28-42d, 42-91d).It was found that patients who started radiotherapy at 42d after surgery had a better prognosis than those who started radiotherapy within 28d after surgery.Kaidar-person [33] also found that patients lived longer who started radiotherapy more than 42d.These results are conflicted with the conclusions from the early comprehensive analysis by Lauwrence (that the prognosis of patients is poor while radiotherapy delayed over 6 weeks) .However, no radiobiological results have been reported to explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The most representative article published by Nathan [27] ,which included 2,535 patients with high-grade glioma and was divided into three groups according to different time intervals (0-28d, 28-42d, 42-91d).It was found that patients who started radiotherapy at 42d after surgery had a better prognosis than those who started radiotherapy within 28d after surgery.Kaidar-person [33] also found that patients lived longer who started radiotherapy more than 42d.These results are conflicted with the conclusions from the early comprehensive analysis by Lauwrence (that the prognosis of patients is poor while radiotherapy delayed over 6 weeks) .However, no radiobiological results have been reported to explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…We selected a retrospective cohort of patients receiving treatment for high‐grade gliomas under the Stupp protocol using a validated algorithm for administrative claims databases . To be eligible for study inclusion, patients were required to have undergone incident craniotomy on or after January 1, 2010; had initiated radiation therapy within 91 days of surgical resection; had initiated temozolomide within 91 days of craniotomy; and had continuous enrollment during the 1 year before craniotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with glioblastoma have a 5‐year survival rate ranging between 0.5% and 4.7% in the United States . Standard care for incident (first‐time) high‐grade glioma includes maximal surgical resection followed by radiotherapy and concurrent/adjuvant temozolomide, a treatment regimen referred to here as the Stupp protocol . Nearly all glioblastoma cases recur even in instances of apparent complete removal of the tumor .…”
mentioning
confidence: 99%
“…В исследовании, включившем 4 584 пациентов с глиобластомой, было обнаружено, что увеличение времени начала лучевой терапии до 4-6 нед после операции является безопасным и может быть умеренно выгодным [25]. При этом начало адъювантного лечения в течение 3-4 нед после операции может иметь отрицательное прогностическое значение [26]. Результаты, полученные в нашем исследовании, показали, что безрецидивная выживаемость значи-clinical studies мо выше у пациентов, которым курс ТХЛТ начат через 6 и более недель после оперативного вмешательства.…”
unclassified
“…Результаты, полученные в нашем исследовании, показали, что безрецидивная выживаемость значи-clinical studies мо выше у пациентов, которым курс ТХЛТ начат через 6 и более недель после оперативного вмешательства. Полученные результаты соответствуют литературным данным и могут быть обусловлены как отбором пациентов с меньшей скоростью прогрессирования опухоли, так и уменьшением послеоперационной гипоксии в перифокальной области в указанные сроки [25,26].…”
unclassified